Pesan Editorial dalam Majalah Risalah - Nuryadin, Taufik (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2017)
Messages disseminated in the form of mass media news (news) and opinions (views), all of which are general (public), because it is intended for the public and the public interest. Among both have a fairly close relationship, because they view emerging or published in newspapers, usually take a topic or news that was warm diperbincangakan society. Editorial or editorial included into the views or opinions; in addition to corner, caricature, letters or writing on behalf (by line story) that specifically fill the opinion pages or page opinion. So no wonder, if the writings put forward opinions rather than facts. However, the presence of these sections is expected to give a feel of its own and has a typical value and interesting to read. The results showed some conclusions. First, the organization category message, indiktif pattern dominates. Second, the category of message structure, pattern of the pros and cons are more. Third, the category of the call message, shows the message composed by the most emotional motives.